Plan estratégico y reposicionamiento de marca para la empresa amoblarte dedicada a la fabricación de productos mobiliarios en la ciudad de Tunja, Boyacá - Amaya Alba, Brenda Michell; Gutiérrez Garay, Sindy Yulieth (Universidad Antonio Nariño, 2023)
This research project will expose the different strategies that were implemented to carry out the repositioning through a marketing plan for the company Amoblarte, dedicated to the manufacture of school and office furniture in the city of Tunja, which has more than 20 years of experience in the manufacture and marketing of these products locally; due to the health crisis COVID 19 that spread in Colombia in March 2020, which has affected the development of the market in general and in this case that of Amoblarte which had to temporarily close its doors to the public and survive with very few resources and financial aid in order not to let the company fall completely, hoping that the market could soon be reactivated so that it could re-emerge and return to its daily tasks. Although the market returned to activity at a high percentage more than a year and a half ago, the company has not managed to get out of its stagnation and as a result a deficit in the economic and financial situation arises.